2023
DOI: 10.1111/epi.17778
|View full text |Cite
|
Sign up to set email alerts
|

Placental disposition of cannabidiol: An ex vivo perfusion study

Erez Berman,
Natalia Erenburg,
Ron Beloosesky
et al.

Abstract: ObjectiveIn the absence of safety data in humans, the use of cannabidiol (CBD) is not recommended during pregnancy. Yet >50% of pregnancies in women with epilepsy are unintended, making fetal exposure to CBD possible. As a small‐molecule, highly lipid‐soluble drug, CBD is likely to distribute into the placenta and cross it. To estimate the placental distribution profile of CBD and its potential short‐term placental effects, we conducted an ex vivo perfusion study in human placentas.MethodsPlacentas were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In vivo studies have demonstrated a THC fetal/maternal steady-state plasma concentration ratio below one third, 22 and about one fifth for Cannabidiol (CBD). 23 Two cannabinoid receptors have been described: CB 1 and CB 2 . 24 Endogenous cannabinoids, similarly to exogenous THC, lead to a decreased vascular tone, increased blood pressure and increased vascular blood flow.…”
Section: F I G U R E 3 Associations Between Antenatal Cannabis Use An...mentioning
confidence: 99%
“…In vivo studies have demonstrated a THC fetal/maternal steady-state plasma concentration ratio below one third, 22 and about one fifth for Cannabidiol (CBD). 23 Two cannabinoid receptors have been described: CB 1 and CB 2 . 24 Endogenous cannabinoids, similarly to exogenous THC, lead to a decreased vascular tone, increased blood pressure and increased vascular blood flow.…”
Section: F I G U R E 3 Associations Between Antenatal Cannabis Use An...mentioning
confidence: 99%